2003
DOI: 10.1207/s15402010bsm0102_2
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Hypnotic Treatments for Insomnia Subtypes

Abstract: This investigation compared progressive muscle relaxation plus cognitive distraction (PMR/CD), hypothesized to better improve sleep onset, versus sleep restriction and stimulus control (SR/SC), hypothesized to better improve sleep maintenance, versus a flurazepam (Dalmane) positive contrast condition (MED) and a sleep hygiene education minimal treatment control condition (SHE). Participants with chronic insomnia (N = 53), completed 2 baseline weeks of sleep diaries, and were randomly assigned to a treatment gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 18 publications
0
9
0
4
Order By: Relevance
“…In a systematic review, Taylor and Roane (2010) pointed out that PMR, among several recommended psychological treatments for the management of sleep disturbance, had the best research support. Waters et al (2003) found that PMR had greater effect upon sleep onset than other non-pharmacologic approaches, like sleep restriction or stimulus control. PMR can relax the muscles of the whole body and decrease the nervous tension, improving the sleep quality.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In a systematic review, Taylor and Roane (2010) pointed out that PMR, among several recommended psychological treatments for the management of sleep disturbance, had the best research support. Waters et al (2003) found that PMR had greater effect upon sleep onset than other non-pharmacologic approaches, like sleep restriction or stimulus control. PMR can relax the muscles of the whole body and decrease the nervous tension, improving the sleep quality.…”
Section: Discussionmentioning
confidence: 88%
“…Waters et al . () found that PMR had greater effect upon sleep onset than other non‐pharmacologic approaches, like sleep restriction or stimulus control. PMR can relax the muscles of the whole body and decrease the nervous tension, improving the sleep quality.…”
Section: Discussionmentioning
confidence: 95%
“…In one of these studies, CBT showed better results than zopiclone; 25 in the other study, flurazepam was superior to progressive muscle relaxation plus cognitive distraction (PMR/ CD), sleep restriction and stimulus control (SR/SC) or sleep hygiene education. 28 Most of the studies compared mind-body intervention with no treatment (waiting-list control). However, two studies showed that mind-body interventions can improve sleep quality of long-term hypnotic drug users.…”
Section: Resultsmentioning
confidence: 99%
“…It is presented along with other interventions 21,24,25,30 like CBT or an active control. 28 Considering that many insomniacs present "bad" habits before sleep, these instructions per se can change the quality of sleep.…”
Section: Questionnairesmentioning
confidence: 99%
“…47,49 Nightly insomnia symptoms (sleep onset or sleep maintenance problems or EMA) have also been associated with different disease characteristics [50][51][52][53][54][55][56] and treatment responses. 57,58 More recently, the heterogeneity driven by objective TST has garnered attention. A number of studies have highlighted differential outcomes associated with short versus long objective sleep.…”
Section: Discussionmentioning
confidence: 99%